2021
DOI: 10.1007/s00330-021-08251-8
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation in multicenter rectal MRI data and their effect on radiomics feature reproducibility

Abstract: Objectives To investigate sources of variation in a multicenter rectal cancer MRI dataset focusing on hardware and image acquisition, segmentation methodology, and radiomics feature extraction software. Methods T2W and DWI/ADC MRIs from 649 rectal cancer patients were retrospectively acquired in 9 centers. Fifty-two imaging features (14 first-order/6 shape/32 higher-order) were extracted from each scan using whole-volume (expert/non-expert) and single-sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
(59 reference statements)
2
17
0
Order By: Relevance
“…These observations are consistent with the findings of Schurink et al [ 45 ], who found significant intercenter variation in multicenter rectal MRI data, with greater variation in DW images and ADC maps compared to T2w images, mainly related to hardware and image acquisition protocols. They further state that such variations will likely negatively influence subsequent analysis if not corrected for [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are consistent with the findings of Schurink et al [ 45 ], who found significant intercenter variation in multicenter rectal MRI data, with greater variation in DW images and ADC maps compared to T2w images, mainly related to hardware and image acquisition protocols. They further state that such variations will likely negatively influence subsequent analysis if not corrected for [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…These observations are consistent with the findings of Schurink et al [ 45 ], who found significant intercenter variation in multicenter rectal MRI data, with greater variation in DW images and ADC maps compared to T2w images, mainly related to hardware and image acquisition protocols. They further state that such variations will likely negatively influence subsequent analysis if not corrected for [ 45 ]. Even though imaging processing and data harmonization were applied in this study prior to network training and testing, our results indicate that further development of a dedicated data pre-processing pipeline is necessary that specifically addresses the inhomogeneities of a multicenter dataset [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…A study by Zhang et al 34 focusing on intensity histogram features and texture features of primary liver cancer demonstrated that most features were significantly influenced by different b-values of DWI. Schurink et al 35 found greater variations in features derived from ADC compared to T2 weighted images from 649 rectal cancer patients across nine centers. Most variation in ADC values could be explained by acquisition and scanner settings instead of essential biological differences.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can neither exclude features based on their interobserver reproducibility nor quantitatively evaluate the agreement between readers. However, Schurink et al 35 showed a relatively minor impact on feature reproducibility from segmentation variation and different annotation software. Lastly, there is a lack of external validation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A further 20 were excluded from the review altogether for not reporting any details. This large degree of variation highlights a need for a standard for reporting details on tumor segmentation, in analogy to other established radiological practices [ 19 ].…”
Section: Discussionmentioning
confidence: 99%